UJI KEBERADAAN ESCHERICHIA COLI PADA AIR MINUM SEBAGAI SALAH SATU INDIKATOR FAKTOR PENYEBAB STUNTING DI KELURAHAN SIDANEGARA CILACAP - Susanti; Sarwa; Dini Puspodewi (Jurnal Profesi Bidan Indonesia, 2025)
Background: Stunting is a condition of impaired growth and development in children resulting from chronic malnutrition, especially during the first 1,000 days of life. Environmental factors such as poor access to clean water and inadequate sanitation significantly increase the risk of infections that impact a child’s growth. One of the indicators of environmental contamination is the presence of Escherichia coli (E. coli) in drinking water, which suggests fecal pollution and poses serious health risks. Purpose: This study aimed to identify the presence of E. coli in drinking water consumed by residents of Sidanegara Village, Cilacap, as a contributing factor to the high prevalence of stunting in the area. Method: This was a descriptive study using a laboratory-based approach. A total of 36 groundwater samples were collected from household wells in RT 08, Sidanegara Village. The samples were examined at the UNAIC Microbiology Laboratory using selective and differential media including EMBA, Lactose Broth, and BGLBB to detect E. coli contamination. Results: The laboratory tests revealed that 6 out of 36 water samples (16.7%) were positive for E. coli, as indicated by the presence of metallic green sheen colonies on EMBA media—characteristic of E. coli growth. Conclusion: The detection of E. coli in household drinking water suggests significant fecal contamination, which poses a risk for diarrheal diseases in children. Recurrent infections can interfere with nutrient absorption, ultimately contributing to stunting. Therefore, ensuring access to clean water and proper sanitation is essential for stunting prevention efforts